The meaning of 'great mountain' in Zechariah 4:71 - O'Kennedy, Daniël Francois (Old Testament essays, 2008)
The book of Zechariah contains a large amount of visionary material and oracles. Sometimes it is difficult to interpret the different metaphors and symbols used in this material. In most instances these symbols are not explained in the Hebrew text. One of these difficult symbols is the reference to lwdghArh (great mountain) in Zechariah 4:7. The question posed by this article is: what is the real meaning of these words? Scholars have offered different hypotheses to answer this question. The 'mountain' was interpreted inter alia as a fictional mountain; Mount Gerizim; opposite powers or world empires; a specific person or group of persons; and a heap of rubble at the temple site. This article evaluates the different hypotheses and suggests a possible interpretation, namely that it must be understood in a holistic and open-ended way, referring to a 'mountain' of problems or adversity that could range from a heap of temple rubble to hostile powers.